Relationship between working conditions and psychological distress experienced by junior doctors in the UK during the COVID-19 pandemic: a cross-sectional survey study. Issue 8 (23rd August 2022) - Dunning, Alice; Teoh, Kevin; Martin, James; Spiers, Johanna; Buszewicz, Marta; Chew-Graham, Carolyn; Taylor, Anna Kathryn; Gopfert, Anya; Van Hove, Maria; Appleby, Louis; Riley, Ruth
Abstract : Objectives: This paper explored the self-reported prevalence of depression, anxiety and stress among junior doctors during the COVID-19 pandemic. It also reports the association between working conditions and psychological distress experienced by junior doctors. Design: A cross-sectional online survey study was conducted, using the 21-item Depression, Anxiety and Stress Scale and Health and Safety Executive scale to measure psychological well-being and working cultures of junior doctors. Setting: The National Health Service in the UK. Participants: A sample of 456 UK junior doctors was recruited online during the COVID-19 pandemic from March 2020 to January 2021. Results: Junior doctors reported poor mental health, with over 40% scoring extremely severely depressed (45.2%), anxious (63.2%) and stressed (40.2%). Both gender and ethnicity were found to have a significant influence on levels of anxiety. Hierarchical multiple linear regression analysis outlined the specific working conditions which significantly predicted depression (increased demands (β=0.101), relationships (β=0.27), unsupportive manager (β=−0.111)), anxiety (relationships (β=0.31), change (β=0.18), demands (β=0.179)) and stress (relationships (β=0.18), demands (β=0.28), role (β=0.11)). Conclusions: The findings illustrate the importance of working conditions for junior doctors' mental health, as they were significant predictors for depression, anxiety and stress. Therefore, if the mental health of junior doctors is to be improved, it is important that changes or interventions specifically target the working environment rather than factors within the individual clinician.